2013
DOI: 10.1165/rcmb.2012-0403oc
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations by DNA Methylation in House Dust Mite–Induced Airway Hyperresponsiveness

Abstract: Asthma is one of the most prevalent chronic lung diseases, affecting 235 million individuals around the world, with its related morbidity and mortality increasing steadily over the last 20 years. Exposure to the environmental allergen, house dust mite (HDM), results in airway inflammation with a variable degree of airway obstruction. Although there has been much experimental work in the past using HDM challenge models to understand mechanistic details in allergic inflammation and airway hyperresponsiveness (AH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…This is in agreement with our previous study showing that HDM-induced AHR was associated with the epigenetic alterations of Pde4d (25). Furthermore, we showed that the epigenetic alteration of PDE4D was associated with the abnormal increase in cell proliferation, migration, and histamine-induced Ca 21 response in asthmatic ASMCs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with our previous study showing that HDM-induced AHR was associated with the epigenetic alterations of Pde4d (25). Furthermore, we showed that the epigenetic alteration of PDE4D was associated with the abnormal increase in cell proliferation, migration, and histamine-induced Ca 21 response in asthmatic ASMCs.…”
Section: Discussionsupporting
confidence: 93%
“…DNA methylation changes are associated with asthma (19,20) and linked to specific triggers of asthma, such as pollutant exposures (21-24). We previously reported that acute exposure to house dust mite (HDM) induced AHR in a mouse model, and the AHR induction was associated with epigenetic modulations of genes related to ASMC proliferation and contraction (25,26). Specifically, we found promoter demethylation of phosphodiesterase 4D (Pde4d) gene in tracheal ASMCs isolated from HDM-exposed mice.…”
mentioning
confidence: 92%
“…Hypomethylation of the PDE4D isoform was recently shown in mice and was related to house dust mite exposure. 16 However, we did not identify this in EA. The potential effects due to asthma medications may also be important in this regard as prolonged β-adrenoreceptor stimulation has been associated with increased PDE4B mRNA expression in human monocytes.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, recent studies confirmed the role of different environmental conditions on DNA methylation 13 and association of such modifications in the pathogenesis of asthma. [14][15][16][17] The genome-wide DNA methylation profiling of whole blood or PBMCs facilitated the identification of many altered gene loci. However, few studies attempted to identify the contribution of particular cell types in the disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that dynamic changes in DNA methylation can provide a possible mechanistic explanation for the link between exposure to allergens and airway hyperresponsiveness [84,85]. Changes in DNA methylation can affect asthma pathogenesis [86] by modulating the expression of disease-related genes [87].…”
Section: Effects Of Diet On Epigenetic Regulation In Bronchial Asthmamentioning
confidence: 99%